2010
DOI: 10.1038/modpathol.2009.141
|View full text |Cite
|
Sign up to set email alerts
|

Low membranous expression of β-catenin and high mitotic count predict poor prognosis in endometrioid carcinoma of the ovary

Abstract: Mutations in the b-catenin gene are common in ovarian endometrioid carcinoma. Few studies have addressed the association of b-catenin expression with tumor characteristics and patient outcome, yielding controversial results. The purpose of this study was to retrospectively assess the expression of b-catenin in ovarian endometrioid carcinoma and correlate its expression with the Gynecologic Oncology Group's (GOG) grading system, clinicopathological characteristics, and patient survival. A total of 49 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…A major finding in our study was the predominately membranous localization of beta-catenin, which among STS has only been described in uterine leiomyosarcomas [21]. Since, membranous beta-catenin expression was low, if any, in our liposarcomas, definite conclusion about its association with the low metastatic potential of the majority of these tumors can not be drawn [22,23]. …”
Section: Discussionmentioning
confidence: 74%
“…A major finding in our study was the predominately membranous localization of beta-catenin, which among STS has only been described in uterine leiomyosarcomas [21]. Since, membranous beta-catenin expression was low, if any, in our liposarcomas, definite conclusion about its association with the low metastatic potential of the majority of these tumors can not be drawn [22,23]. …”
Section: Discussionmentioning
confidence: 74%
“…One of the possible mechanisms of WNT/β-catenin pathway alteration involves mutations of the β-catenin gene (CTNNB1), which are found in endometrioid subtype of ovarian cancer [19-21]. Additionally, aberrant expression of β-catenin, E-cadherin and WNT-1 was observed in ovarian carcinoma [22-27]. The prognostic role of β-catenin and E-cadherin are disputed, while their impact on response to chemotherapy has never been evaluated in ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recently, investigators also reported that patients with endometrioid OvCa with increased membrane A-catenin protein expression had decreased PFS and increased platinum resistance. 3 To further evaluate Wnt pathway genes as potential biomarkers for OvCa survival and chemotherapy response, we analyzed associations of Wnt pathway genes with survival outcomes among patients with high-grade serous OvCa treated with IP or IV chemotherapy.…”
mentioning
confidence: 99%